Einstein-Klein-Gordon System in Higher Dimensional - Mirda Prisma Wijayanto; Fiki Taufik Akbar Sobar; Bobby Eka Gunara (Indonesian Journal of Physics, 2021)
In this present work, we study the Einstein equation coupled with the nonlinear Klein-Gordon equation. We obtain Ricci tensor, scalar curvature, and Einstein equation of the Einstein-Klein-Gordon system in higher dimensional. If we put D=4, our formulations reduce to the four dimensional Einstein-Klein-Gordon system.